The Role of Depression in Medication Adherence Among Heart Failure Patients. (June 2014) - Tang, Hsin-Yi (Jean); Sayers, Steven L.; Weissinger, Guy; Riegel, Barbara
The purpose of the study was to explore the association between depression and medication adherence in heart failure (HF) patients. Studies have shown that people with depression are likely to be nonadherent to their prescribed medication treatment. But other studies suggest that nonadherence may be overestimated by people with depression. A total of 244 adults with Stage C HF completed the study. Self-reported medication adherence was obtained using the Basel Assessment of Adherence Scale (BAAS); objective data on medication adherence were collected using the electronic Medication Event Monitoring System (MEMS). Depression was measured via self-report with the Patient Health Questionnaire (PHQ-9). There was a significant difference between depressed and nondepressed participants in self-reported medication nonadherence ( p = .008), but not in objectively measured medication nonadherence ( p = .72). The depressed sample was 2.3 times more likely to self-report poor medication adherence than those who were nondepressed ( p = .006).